2022
DOI: 10.3390/agronomy12020379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilisation with Ash from Biomass Combustion on the Mechanical Properties of Potato Tubers (Solanum tuberosum L.) Grown in Two Types of Soil

Abstract: The aim of the research was to determine the effect of fertilising with various doses of ash from biomass combustion (D2–D6) compared to control plots and classic NPK (D1) fertiliser on the morphological and mechanical properties of potato tubers (Solanum tuberosum L.). The field experiment was carried out in the years 2019–2021 (south-eastern Poland, 49°59′ N, 21°57′ E) on two types of soil: Gleyic Chernozem (silty loam) and Haplic Luvisol (silt). The values of mechanical parameters, such as the peel and fles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…The mineral composition of the ash used was dominated by potassium ranging from 99.6 kg ha −1 year −1 (D1) to 469 kg ha −1 year −1 (D6). However, potassium was not present in the control fertilizer [5]. The two-factor analysis of variance showed a significant statistical influence of all the factors analyzed on the phosphorus content in starch.…”
Section: The Content Of Mineral Elements In Starchmentioning
confidence: 83%
See 3 more Smart Citations
“…The mineral composition of the ash used was dominated by potassium ranging from 99.6 kg ha −1 year −1 (D1) to 469 kg ha −1 year −1 (D6). However, potassium was not present in the control fertilizer [5]. The two-factor analysis of variance showed a significant statistical influence of all the factors analyzed on the phosphorus content in starch.…”
Section: The Content Of Mineral Elements In Starchmentioning
confidence: 83%
“…Mineral nitrogen fertilizer (in the form of RSM ® 32% N (aqueous solution of urea ammonium nitrate; density, 1.32 kg/dm −3 )), monoammonium phosphate (MAP) NH 4 H 2 PO 4 (12% N-NH 4 52% P 2 O 5 (22.7% P)), and phosphorus (in the form of Monoammonium phosphate (MAP)) were constant. In variants D2 to D6, ashes from forest biomass combustion (70%) and agricultural biomass (30%) were used as fertilizer [5]. The potatoes were planted in the third decade of April, when the soil at a depth of 10 cm reached a temperature of approximately 6-8 • C. The cast used 40 thousand plants per ha.…”
Section: Design Of Field Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zapałowska et al 20 report that the application of biomass ash at a rate of 12.8 t ha −1 increased the potassium content of Jerusalem artichoke plants to 5.63 g K kg −1 . Szpunar-Krok et al 21 found that application of biomass ash fertilizer increases potato tuber yields and resistance to mechanical damage under quasi-static loads. The use of biomass ash as a fertilizer may be a sustainable strategy to maintain the availability of elements including phosphorus in soils 11 thus improving their agricultural suitability.…”
Section: Introductionmentioning
confidence: 99%